Male Field Cricket Songs Are Altered After Aggressive Interactions - Bunting, Jamie E.; Hedrick, Ann V. (Frontiers in Ecology and Evolution, 2018)
To address the hypothesis that male acoustic sexual advertisement signals might be indicators of aggressiveness, in addition to chemical signals, we examined the relationship between levels of aggression/dominance status and acoustic sexual advertisement signals in the field cricket Gryllus integer. Males were paired in aggression trials and recorded the night before and the night after the trial. This allowed us to test whether aggression is inherently linked to song phenotypes, or whether aggressive interactions cause males to alter their songs. We found that dominant (winning) males signaled with higher energy, amplitude and power the night after winning an aggressive encounter, but not before the encounter. Time spent calling and the number of calling bouts were unrelated to aggression, whereas whereas winning males increased their bout lengths after winning, and losing males decreased their bout lengths after losing.